2021
DOI: 10.1016/j.crad.2020.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Value of quantitative sound touch elastography of tissues around breast lesions in the evaluation of malignancy

Abstract: To assess the value of quantitative analysis of sound touch elastography of tissues around breast lesions to facilitate the evaluation of malignancy of the lesions. MATERIALS AND METHODS: With the permission of the Ethics Committee, every patient signed informed consent forms before the study. One hundred and eighty-two solid breast lesions were analysed retrospectively. Postoperative histopathology proved that 63 lesions were malignant and 119 were benign. All lesions were examined by two-dimensional ultrason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
1
12
2
Order By: Relevance
“…Our study offered the automatically plotted 1-3 mm shells around the breast lesion, which helped to calculate the maximum YM at the tumor border. However, unlike previous studies [20,[23][24][25], our results revealed that the presence of the stiff rim sign had the highest diagnostic accuracy rather than those quantitative SWE parameters, especially the E max of 1-3mm shell. We supposed that this is because the shell, which is composed of glandular tissue, may also exist around benign tumors, thus affecting the diagnostic performance of the E max at the shell [12].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study offered the automatically plotted 1-3 mm shells around the breast lesion, which helped to calculate the maximum YM at the tumor border. However, unlike previous studies [20,[23][24][25], our results revealed that the presence of the stiff rim sign had the highest diagnostic accuracy rather than those quantitative SWE parameters, especially the E max of 1-3mm shell. We supposed that this is because the shell, which is composed of glandular tissue, may also exist around benign tumors, thus affecting the diagnostic performance of the E max at the shell [12].…”
Section: Discussioncontrasting
confidence: 99%
“…The desmoplastic reaction caused by the peritumoral infiltration of cancer cells into the interstitial tissues increases the peritumoral stiffness 9 , 21 , 22 . Recent studies using this shell-based analysis found that the E max of 1-3mm shell was the most accurate for differential diagnosis of benign and malignant breast lesions 20 , 23 - 25 . Our study offered the automatically plotted 1-3 mm shells around the breast lesion, which helped to calculate the maximum YM at the tumor border.…”
Section: Discussionmentioning
confidence: 99%
“…10 Shear wave ultrasound elastography allows to quantitatively assess tissue stiffness, but is used less often in tendinopathy diagnostics. It is well-established for visualization of stiffness of liver, 11 breast, 12 prostate, 13 thyroid, 14 shoulder tendons, 15 and tongue muscle 16 lesions. It is also regarded as a promising tool for the diagnosis of Achilles tendinopathy and patellar tendons in routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the CNN models used in the diagnosis of breast cancer have been based on the US or SWE images of intratumoral tissue rather than peritumoral tissue. Judging from the results of previous studies, peritumoral stiffness of breast lesions is an accurate predictor of breast cancer [9][10][11][12]. However, based on the traditional SWE technology, it is di cult to obtain accurate SWE image of the peritumoral tissue, and it is hard to estimate which width of the peritumoral tissue should be evaluated to provide the optimal diagnostic index of benign and malignant lesions [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have con rmed that the assessment of peritumoral stiffness of breast lesions can improve the accuracy of SWE in predicting breast cancer, considering desmoplastic reaction and tumor cell in ltration into the peritumoral stroma [9][10][11][12]. Several other studies have demonstrated that the peritumoral invasion is an independent prognostic factor signi cantly associated with an increased risk of relapse and death in node-negative breast cancer patients [13,14].…”
Section: Introductionmentioning
confidence: 99%